2020
DOI: 10.1111/gbb.12651
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of array‐CGH in the ADHD clinics: A comparative study

Abstract: Attention deficit hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorder with a worldwide prevalence of about 5%. The disorder is characterized by inattentive, hyperactive and impulsive behavior and is often comorbid with other neuropsychiatric conditions. Array comparative genomic hybridization (array‐CGH) testing has been proved to be useful to detect chromosomal aberrations in several neuropsychiatric conditions including autism spectrum disorders (ASD) and intellectual disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Depending on array model and platform, array comparative genomic hybridization (aCGH) allows identifying the presence of CNVs (deletions and duplications) at the whole genome level with a resolution down to just ~5-100 Kb. Hence aCGH, as already extensively described in the literature, has been confirmed as a "gold standard" first-level test in the genetic diagnosis of ASD (Aradhya et al, 2007;Miller et al, 2010;Sanders et al, 2015) and for neurodevelopmental disorders in general (Baccarin et al, 2020). Much evidence revealed that copy number variants (CNVs) detected by aCGH are major contributors to ASD pathogenesis in up to 10%-15% of affected children (Miller et al, 2010;Sebat et al, 2007).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Depending on array model and platform, array comparative genomic hybridization (aCGH) allows identifying the presence of CNVs (deletions and duplications) at the whole genome level with a resolution down to just ~5-100 Kb. Hence aCGH, as already extensively described in the literature, has been confirmed as a "gold standard" first-level test in the genetic diagnosis of ASD (Aradhya et al, 2007;Miller et al, 2010;Sanders et al, 2015) and for neurodevelopmental disorders in general (Baccarin et al, 2020). Much evidence revealed that copy number variants (CNVs) detected by aCGH are major contributors to ASD pathogenesis in up to 10%-15% of affected children (Miller et al, 2010;Sebat et al, 2007).…”
Section: Introductionmentioning
confidence: 90%
“…Autism spectrum disorder (ASD) encompasses a group of neurodevelopmental disorders (the "autisms") characterized by impairment in social interaction and communication, including deficits in social reciprocity, accompanied by restricted interests, repetitive patterns of behavior, and abnormal sensory processing (American Psychiatric Association, 1994;Persico et al, 2020). Its prevalence rates range from 1/54 children and 1/45 adults in the United States (Dietz et al, 2020;Maenner et al, 2020), to 1/87 children in Italy and 1/102 adults in England (Brugha et al, 2011;Narzisi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, CHRNA7 (coding the α7-nAChR (Jensen et al 2005)), has been associated with ASD, as has been CHRFAM7A (Bacchelli et al 2015) -an exclusively human and highly polymorphic hybrid gene consisting of a duplicated portion of CHRNA7 fused to exons A-E of FAM7A (Gault et al 1998;Wall et al 2009;Pinto et al 2010;Casey et al 2012;Huguet et al 2013;Bacchelli et al 2015;Gillentine and Schaaf 2015;Gillentine et al 2017). CHRNA7 has also been implicated in ADHD (Baccarin et al 2020;Gillentine et al 2017;Gillentine and Schaaf 2015;Sinkus et al 2015;Valbonesi et al 2015), but not all studies have not replicated this finding (Kent et al 2001;Faraone et al 2005;Ross 2012).…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…CHRFAM7A has also been associated with ADHD (Baccarin et al 2020;Williams et al 2012), but replication is required to confirm this association. Another gene, CHRNA4, codes for the α4-nAChR and has been identified as a candidate gene for ASD, but this gene seems to only play a role in specific cases (i.e.…”
Section: Molecular Geneticsmentioning
confidence: 99%